Carers’ experiences of assistive technology use in dementia care: a cross sectional survey - Vimal Sriram (BMC Geriatrics, 2021)
Abstract Background Assistive Technology (AT) supports persons with dementia and their carers (family, friends and neighbours), yet little is known about experiences and the impact of AT on carers. We report on an exploratory survey that examined the types, uses, costs and impact of AT on carers as well as their quality of life. Methods A cross-sectional survey using the Carers Assistive Technology Experience Questionnaire collected data from carers in the UK, who used at least one AT in the previous year and provided more than 10 h of care for a person with dementia, living at home. Carers completed the questionnaire online or on paper and information on AT, socio-demographic details, and Short-Form Health Survey (SF-12) data were collected. Descriptive and inferential statistics were used to report results and draw conclusions. Results Data from 201 carers was analysed. Smartphones and tablet computers were the most frequently used AT. AT were used predominantly for safety, communication, and reminders. Carers usually make decisions on buying and continued use of AT. Multiple AT devices were used in the care of persons with dementia and number of AT used was associated with perceived satisfaction. Satisfaction with AT was not related to age, living arrangements and relationship of carers. From the SF-12, Mean Physical Component Score was 49.19 (95%CI- 47.75 to 50.63) and Mental Component Score was 45.37 (95%CI- 43.93 to 46.80). Women, carers in the 46–65 age group and carers who were not extremely satisfied with AT had lower MCS scores. Carers who lived with the person with dementia and older carers had lower PCS scores. Conclusions Carers report that AT has a beneficial impact. Carers use multiple ATs, perceive AT to be satisfactory and recommend AT use to others. To support carers, we recommend establishment of centrally funded information sources and a loan store for AT. Further research on incremental addition of AT and changes to formal/paid care because of using AT should be undertaken. Practitioners, academics, manufactures and policy makers should consider the experiences of carers in research, development and use of AT to facilitate improved community living of people with dementia.